Determinants of savings behaviour among Muslims in Malaysia: an empirical investigation / Shafinar Ismail … [et al.] - Ismail, Shafinar; Jahya, Arnida; Md Sahiq, Aqilah Nadiah; Mohamed, Rozita Naina; Khairuddin, Nadia Syazwani (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Savings behaviour differs significantly across countries. It is important to identify the savings behaviour as people prefer to spend rather than to save. Even though it is important, however, there are lacks of research on savings behaviour, particularly on how social influence and financial knowledge affects the savings behaviour. Thus, the aim of the study is to identify how the social influence and financial knowledge affects the savings behaviour among Muslims in Malaysia. This study employs mixed methods for the purpose of data collection. Quantitative approach (a questionnaire survey) has been implemented, followed by semi-structured interviews. Semi¬ structured interviews were conducted to cross-check the quantitative findings. Both the quantitative and qualitative data involves coding; the responses are computerised in a format appropriate for using Nvivo 8.0 and SPSS 20.0 in the analyses. The result indicates that social influence and financial knowledge do give significant influence towards the saving behaviour among Muslims.